Fiscal Policy and External Performance : The Turkish Experience. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
In 1980 Turkey embarked on a far-reaching stabilization and liberalization program, which contributed to export-led growth and a significant movement toward both domestic and external equilibrium. Later, as fiscal policy was partly reoriented from a restrictive to an expansionary stance while adhering to a flexible exchange rate policy, inflationary pressures intensified but the external current account did not deteriorate. Counterfactual simulations, performed with a computational general equilibrium model, suggest that Turkey would have experienced a significantly lower inflation rate, with only a small reduction in growth, if it had adopted a less expansionary fiscal stance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet